2014
DOI: 10.1128/jcm.02571-13
|View full text |Cite
|
Sign up to set email alerts
|

Early Kinetics of Plasma Cytomegalovirus DNA Load in Allogeneic Stem Cell Transplant Recipients in the Era of Highly Sensitive Real-Time PCR Assays: Does It Have Any Clinical Value?

Abstract: We report that in a population of allogeneic stem cell transplant recipients, determination of the viral doubling time (dt) of the cytomegalovirus (CMV) DNA plasma load predicted the eventual need for inception of preemptive antiviral therapy, whereas the level of the initial plasma CMV DNA load did not. The data thus indicated that determination of the dt of CMV DNA may be useful in the therapeutic management of CMV infection in this clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 13 publications
2
28
1
Order By: Relevance
“…We believe that kinetic analyses of plasma CMV DNA load and routine monitoring of CMV-specific T-cell responses may help to achieve these purposes. In effect, we recently showed that a CMV DNA load doubling time (dt) ≤2 days, anticipated the eventual need of preemptive antiviral with a positive predictive value of 100% [13]. We later reported that treating patients upon dt s ≤2 days led to a significant reduction of the time on antiviral therapy [14].…”
mentioning
confidence: 99%
“…We believe that kinetic analyses of plasma CMV DNA load and routine monitoring of CMV-specific T-cell responses may help to achieve these purposes. In effect, we recently showed that a CMV DNA load doubling time (dt) ≤2 days, anticipated the eventual need of preemptive antiviral with a positive predictive value of 100% [13]. We later reported that treating patients upon dt s ≤2 days led to a significant reduction of the time on antiviral therapy [14].…”
mentioning
confidence: 99%
“…The use of this criterion for the inception of antiviral therapy would have resulted in a number of patients being treated~1 week earlier. 7 We hypothesized that this could possibly result in a reduction in the number of days on treatment. Here, we report on our experience with this therapeutic strategy, already in use at our center for 1 year.…”
mentioning
confidence: 99%
“…The most relevant characteristics of the patients are shown in Table 1. CMV DNA load monitoring in plasma was performed as previously indicated, 3,5,7 using the new RealTime CMV PCR (Abbott Molecular, Des Plaines, IL, USA), whose limit of detection and quantification is 20 copies/mL (95% confidence interval). 8,9 Antiviral therapy with valganciclovir either at conventional doses (900 mg/12 h) or at reduced doses (450 mg/12 h) in patients meeting one or more of the following criteria: o 50 kg body weight, reduction of the glomerular filtrate ⩽ 60 mL/min per 1.73 m 2 , o1000 neutrophils/μL or o 50 000 platelets/μL, was initiated when the CMV dt was ⩽ 2.0 days, or alternatively when the plasma CMV DNA load reached levels of 41000 copies/mL, whichever occurred first.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of methods for CMV surveillance displaying different sensitivities (pp65 antigenemia assay (AG) vs. real-time PCR assays) may account in part for these discrepancies [6]. In this single-center retrospective study, we re-examined this potential association using highly sensitive real-time PCR assays (limit of detection: approximately 20 copies/ml- [6][7][8]) (CMV PCR Kit and the New CMV RealTime PCR assay; Abbott Molecular, Des Plaines, IL, USA) in plasma specimens. We included 92 nonconsecutive patients undergoing Allo-SCT (January 2010-August 2014) for hematological malignancy.…”
mentioning
confidence: 99%